Systemic thrombolysis in the upper extremity deep vein thrombosis - Sadeghi, Roxana (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2011)
Almost 4% of all patients with venous thrombosis have upper extremity deep vein thrombosis (UEDVT) and the incidence of UEDVT increases over time. The frequency of post-thrombotic syndrome (PTS) after UEDVT is not low and upper extremity PTS is a potentially major morbidity that adversely affects quality of life, particularly if the dominant arm is involved. We discuss briefly the role of thrombolytic therapy in the treatment of upper extremity deep vein thrombosis and also the role of systemic thrombolysis in selected patients.